Sovereign Eurobond Liquidity and Yields - Hardy, Daniel (Washington, D.C. : International Monetary Fund, 2022)
Market liquidity is of value to both investors and issuers of securities, and is therefore a crucial factor in asset pricing. For the important asset class of Eurobonds, significant feedback from liquidity to pricing is established, and it is shown that bid-ask spreads (a proxy for market liquidity) and yields are closely related to bond characteristics such as issue volume, time to maturity, the inclusion of collective action clauses, and the jurisdiction of issuance. Debt management offices can choose these characteristics in a way that has economically significant and persistent effects on both liquidity and pricing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Debt Management; Debt; International Financial Markets; International Lending and Debt Problems; Sovereign Debt